(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2013)
Many new developments in the field of information technology have affected modern society in numerous ways, including advancement in communication, education, commerce, and so on. These modern up gradations have brought incredible benefits to the society at large but they have also provided numerous opportunities for various forms of crime, thus making crime a highly profitable avenue. Among the many types of criminal activities, modern technology has allowed money laundering to become an online crime. Money laundering is the process where cash raised from criminal activities is made to look legitimate for re-integration into the financial system. It also refers to the process of concealing the source of money obtained by illicit means. This new type of crime has raised some legal questions about the capability of national and international regulations in relation to current and upcoming issues. These include finding electronic funds transfer records and determining money laundering activity that includes electronic funds transfer. Electronic funds transfer (EFT) is the electronic exchange, transfer of money from one account to another, either within a single financial institution or across multiple institutions, through computer-based systems. Electronic money provides an easy method of transferring value without revealing identity. The increase in the amount of crime indicates the following series of techniques and mechanisms that had been detected in relation to money laundering activity. This research will examine current issues under the light of various regulations, and will put forward some proposals to close the legal vacuum.